Generation of a CRISPR/Cas9-Based Vector Specific for Gene Manipulation in Leishmania major - SALEHI SANGANI, Ghodratollah (Iran J Parasitol, 2019)
BACKGROUND: Gene manipulation strategies including gene knockout and editing are becoming more sophisticated in terms of mechanism of action, efficacy and ease of use. In classical molecular methods of gene knockout, homologous arms are designed for induction of crossing over event in double strand DNA. Recently, CRISPR/Cas9 system has been emerged as a precise and powerful tool for gene targeting. In this effort, we aimed to generate a CRISPR/Cas9-based vector specific for targeting genes in Leishmania parasites. METHODS: U6 and DHFR promoters and neomycin-resistance gene were amplified from genome of L. major (MHRO/IR/75/ER) and pEGFP-N1, respectively. U6 promoter was cloned in pX330 vector which is named as pX330-U6. DHFR promoter and neo resistance gene sequence fragments were fused using a combination of SOE (Splicing by overlap extension)-PCR and T/A cloning techniques. To generate pX-leish, fused fragments su-bcloned into the pX330-U6. Two sgRNAs were designed to target the gp63 gene and cloned in pX-leish. RESULTS: The pX-leish vector was designed for simultaneous expression of cas9 and G418 resistance proteins along with a self-cleaving 2A peptide for efficient separation of the two proteins. In this study pX-leish was designed with 3 features: 1) Compatible promoters with Leishmania parasites. 2) Insertion of antibiotic selection marker 3) Designing an all-in-one vector containing all components required for CRISPR/Cas9 system. CONCLUSION: This modified system would be valuable in genome manipulation studies in Leishmania for vaccine research in future.